Faktor-Faktor yang Mempengaruhi Produksi Gula Kelapa Skala Rumah Tangga - Faza, Amila Layaliya; Wahyuningsih, Sri; Awami, Shofia Nur; Sasongko, Lutfi Aris (Proceedings Series on Physical & Formal Sciences, 2021)
Many coconut plants grow and develop in Tunjungmuli Village which are cultivated by the surrounding community for the manufacture of palm sugar on a household scale. This study aims to determine the existence of constraints, factors that affect the production of palm sugar, and the level of economic efficiency of using palm sugar production factors. The method used is data stabilization, multiple linear regression analysis and marginal product value analysis, data collection is done by interview. Sampling was carried out using the simple random sampling method, which consisted of 36 craftsmen. The results showed that palm sugar production in Tunjungmuli Village, Karangmoncol District, Purbalingga Regency in February-March 2021 decreased due to extreme weather, erratic rains. The use of palm sugar production factors simultaneously has a significant effect on sugar production, the number of workers (0.006), the number of juice (0.000) and the number of plants tapped (0.000). Meanwhile, firewood (0.018) and business experience (0.815) did not have a significant effect on palm sugar production. The efficiency of the use of production factors, the amount of juice and the number of plants tapped has not been efficient because >1. While the number of workers, business experience and firewood <1 is not efficient, it needs to be reduced in use.